To Coerce or to Enable? Exercising Formal Control in a Large Information Systems Project - Heumann, Jakob; Wiener, Martin; Remus, Ulrich; Mähring, Magnus (Journal of information technology, 2015)
In virtually every information systems (IS) project, control is exercised on multiple hierarchical project levels. For example, senior managers exercise control over project team leaders, who in turn exercise control over distinct groups of project team members. Most prior studies have exclusively focused on one specific controller-controllee dyad. As a result, there is little understanding of how IS project control is exercised across different hierarchical levels. To close this research gap, we conducted a case study of a large IS project at a major engineering firm. Our study helps enrich the traditional mode-based typology of control with the dimension of control style, that is, the distinction between enabling and coercive control. Our research contributes novel insights to the IS control literature in three ways: (1) we find that the senior management level and the project management level differ in the use of control style but not in the use of control modes, (2) we identify several factors that influence the choice of a particular control style, and (3) we find that senior managers can influence project activities on lower levels by implementing controls that can be readily emulated by project leaders as well as transmitted through hierarchical levels with little distortion.